2016
DOI: 10.1021/acsami.6b06309
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin Methacrylate Hydrogels as Biomimetic Three-Dimensional Matrixes for Modeling Breast Cancer Invasion and Chemoresponse in Vitro

Abstract: Recent studies have shown that three-dimensional (3D) culture environments allow the study of cellular responses in a setting that more closely resembles the in vivo milieu. In this context, hydrogels have become popular scaffold options for the 3D cell culture. Because the mechanical and biochemical properties of culture matrixes influence crucial cell behavior, selecting a suitable matrix for replicating in vivo cellular phenotype in vitro is essential for understanding disease progression. Gelatin methacryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 86 publications
5
66
0
Order By: Relevance
“…From the SEM images, it can be seen that 2% w/v alginate exhibits more oblong and larger pores, compared with the smaller honeycomb‐like pores in 7.5% w/v GelMA. These results are in accordance with previous work from Yao et al, Arya et al, and Athirasala et al, who demonstrated similar alginate and GelMA hydrogel microstructures. SEM of the cross‐sectional area of a hydrogel obtained from combining the two polymers shows clear differences in architecture and porosity.…”
Section: Resultssupporting
confidence: 94%
“…From the SEM images, it can be seen that 2% w/v alginate exhibits more oblong and larger pores, compared with the smaller honeycomb‐like pores in 7.5% w/v GelMA. These results are in accordance with previous work from Yao et al, Arya et al, and Athirasala et al, who demonstrated similar alginate and GelMA hydrogel microstructures. SEM of the cross‐sectional area of a hydrogel obtained from combining the two polymers shows clear differences in architecture and porosity.…”
Section: Resultssupporting
confidence: 94%
“…For instance, Kaemmerer et al utilized photocrosslinkable gelatin methacrylamide (GelMA) hydrogel to study the growth of ovarian cancer cells [62]. GelMA hydrogel has been demonstrated to be advantageous for tissue engineering and 3D culture of numerous cell types due to the high concentration of matrix metalloproteinase-(MMP) sensitive degradation sites [63][64][65][66][67].…”
Section: D Microengineered Models To Study Tumor Initiation and Growthmentioning
confidence: 99%
“…However, a potential drawback of traditional photocrosslinking techniques is the exposure of the cells to UV light, which could lead to cytotoxicity and/or mutagenesis. Despite this drawback, many studies have confirmed physiologically relevant cell behavior when embedded within GelMA hydrogel [62,64,67].…”
Section: D Microengineered Models To Study Tumor Initiation and Growthmentioning
confidence: 99%
“…Hence, there is a need to develop a 3D matrix which could be used to form spheroids inside the matrix and which can serve as a model for screening of new pharmacological compounds (Hoarau‐Véchot et al, ). There are studies where hydrogels have been used to develop spheroids for ovarian cancer (Kaemmerer et al, ) and breast cancer (Arya et al, ). However, very few studies have been reported for the formation of spheroids in cryogel based matrices (Bäcker et al, ; Göppert et al, ; Kumari, Karande, & Kumar, ; Lee et al, ; Sarkar & Kumar, ).…”
Section: Introductionmentioning
confidence: 99%